Italian in 3 months your essential guide to understanding and speaking Italian - Reynolds, Milena (New York, NY DK Publishing, 2022)
"Everything you need to understand and speak Italian. Free audio app helps you perfect your pronunciation by imitating native speakers. Builds vocabulary through word lists, key phrases, and model sentences. Explains essential grammar. Develops conversation through exercises based on real-life scenarios"--Back cover
"With free audio app"--Cover
Includes index
Keywords: Italian language -- Problems, exercises, etc; Italian language -- Textbooks for foreign speakers -- English; Italian language -- Self-instruction; Italian language -- Spoken Italian; Italian language -- Spoken Italian; Italian language; Problems and exercises; Textbooks